Association of Catechol-O-Methyltransferase Gene rs4680 Polymorphism and Levodopa Induced Dyskinesia in Parkinson's Disease: A Meta-Analysis and Systematic Review. (March 2023) - Dwivedi, Archana; Dwivedi, Nidhi; Kumar, Anand; Singh, Varun K.; Pathak, Abhishek; Chaurasia, R. N.; Mishra, V. N.; Mohanty, Sujata; Joshi, Deepika
Introduction: Long-term levodopa therapy for Parkinson's disease (PD) can cause levodopa induced dyskinesia (LID). Genetic predisposition has a significant role to play in inter-individual heterogeneity in the clinical manifestation of LID. Despite accumulating evidence for the role of COMT gene polymorphism (rs4680) as a genetic basis for LID, to date results have been inconsistent. Early assessment of the Catechol-O-Methyltransferase (COMT) genotype might be helpful to stratify PD patients concerning their individual risk for LID. Method: In this meta-analysis, we have used 9 studies, which were selected through online databases. Statistical analysis was performed using R (v-3.6) software. 5 genetic models have been used in the present study: Allele model (A vs. G), Dominant model (AA+AG vs. GG), Homozygote model (AA vs. GG), Co-dominant/heterozygote model (AG vs. GG), and Recessive model (AA vs. AG + GG). Results: The results indicated a significant association between COMT rs4680 (Val158Met) polymorphism and LID risk. The genotype AA of COMT rs4680 is a risk factor for LID in PD patients under the recessive model (AA vs GG+AG) in the random-effect model. Analysis based on ethnicity showed that COMT rs4680 SNP allele A is a risk factor for LID development in Asian PD patients, while GG genotype is a risk factor for LID development in non-Asian PD patients using different genetic models. Conclusion: The results of the present meta-analysis support that the COMT Val158Met polymorphism is a risk factor for the development of LID in PD patients having ethnic variations. Graphical Abstract